SURVEI PERILAKU MAHASISWA KOTA PADANG DALAM MENGAKSES YOUTUBE BERDASARKAN KARAKTERISTIK PERGURUAN TINGGI MENGGUNAKAN METODE USES AND GRATIFICATIONS - Saputra, Andi (Jurnal Studi Komunikasi dan Media, 2024)
YouTube is currently one of the most widely used multimedia platforms, and students in universities use it. This study aims to understand the behavior and motivation of Padang City students when accessing or watching YouTube videos. This research is quantitative and based on survey methods using questionnaires. The data was processed using descriptive statistical methods. The location of the research was carried out at a state university in Padang City. Their behavior was observed using frequency variables and the duration of time they spent watching YouTube. The data were analyzed based on gender and the character of the universities where they studied. The results of this study show that most college students like entertainment topics when watching YouTube. Of the 439 respondents, most were passive users (92.5%), with the majority of their YouTube watch frequencies being "several times a day," and the duration of each watch was between 10 and 30 minutes. The obstacles to accessing YouTube are still quotas and internet connection. In addition, it was also found that the frequency of watching students from state Islamic religious universities was lower than others. Meanwhile, diploma students are more likely to watch videos that are short in duration.